Effect of carbon addition and cooling rate on lamellar structure of peritectic TiAl-based alloy. (January 2021) - Lapin, J.; Kamyshnykova, K.; Pelachová, T.; Nagy, Š.
Abstract: The effect of carbon addition and cooling rate on the lamellar structure of peritectic Ti-46.5Al–5Nb-0.2B-0.2C (at.%) alloy was studied. The studied alloys with a carbon content of 0.2, 0.5, 0.7 and 1.0 at.% were prepared by vacuum induction melting in graphite crucibles. The as-cast samples were subjected to solution annealing in a single α (Ti-based solid solution) phase field followed by cooling at four constant rates ranging from 5 to 50 °C/min. The increase in carbon content leads to an increase in both start and finish α phase decomposition temperatures. During continuous cooling, the carbon atoms segregate along α2 (Ti3 Al)/γ(TiAl) lamellar interfaces and hinder lateral growth of γ lamellae. The interlamellar spacing decreases with increasing carbon content and increasing cooling rate. A relationship describing the complex influence of carbon content and cooling rate on α2 -α2 interlamellar spacing λ is proposed. Vickers microhardness HVm increases with increasing both the carbon content and cooling rate. The Vickers microhardness depends on interlamellar spacing λ according to the Hall-Petch relationship. Highlights: Interlamellar spacing decreases with increasing carbon content and cooling rate. Vickers microhardness increases with decreasing interlamellar spacing. Relationships for predicting interlamellar spacing and Vickers microhardness are proposed. Segregating carbon atoms and forming carbides hinder lateral growth of lamellae.